Anti-photoageing and anti-melanogenesis activities of chrysin. (1st November 2016) - Zhu, Li; Lu, Yue; Yu, Wan-Guo; Zhao, Xin; Lu, Yan-Hua
Abstract: Context: Melanin plays an important role in preventing skin photoageing by blocking ultraviolet B (UVB). However, East Asian women prefer light and fair skin, therefore they want to keep their skin from photoageing and at the same time reduce the melanin in their skin. Chrysin is a kind of natural flavonoid with luxurious biological activities, which has a very promising effect on achieving this goal. Objective: To elucidate the effects and mechanisms of chrysin on photoageing and melanogenesis. Materials and methods: Human dermal fibroblasts (HDF) and B16 murine melanoma cells were incubated with chrysin (0–25 μM) for 48 h. Anti-photoageing activity was examined in HDF by assessment of synthesis/degradation of collagen I, antioxidative and antisenescent activities through ELISA and colorimetric method. Anti-melanogenesis activity was tested by assessment of melanin, tyrosinase (TYR), melanogenic proteins inhibition activities in B16 cells using colorimetric and ELISA method. Results: Chrysin increased collagen I secretion (50–121.54% at 6.25–25 μM) and chrysin showed anti-photoageing activity by decreasing the degradation of collagen I, repairing oxidation damage and reducing the rate of HDF senescence. Furthermore, chrysin exhibited inhibitory activities with 3.00–20.35% reduction of melanin content at 6.25–25 μM, and inhibited melanin synthesis through the inhibition of TYR activity and the suppression of melanogenic proteins (TYR, TYR-related protein-1/2 and microphthalmia-associated transcription factor) expressions. Discussion and conclusion: Chrysin may have potential for developing a functional cosmetic agent because of its anti-photoageing and anti-melanogenesis activities.